The principle of individual legal responsibility of payer of tax value-added: problems of normative certainty and realization - Пивовар, Юрій Ігорович; Казанцев, Андрій Ігорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The authors revealed the causes of the violation of the constitutional principle of individual legal responsibility of payers of value added tax. Is defined and studied administrative and judicial position into tax disputes related to the deprivation of taxpayer of tax credit in connection with the recognition of fictitious activities of his contractor. Advocated and justified the author’s position on the need for legislative consolidation of the principle of individual liability tax and taxpayers in general and the administration of the value added tax in particular.